Analysis of Femoral Components of Cemented Total Hip Arthroplasty - Singh S.; Harsha A.P. (My University, 2025)
There have been continuous on-going revisions in design of prosthesis in Total Hip Arthroplasty (THA) to improve the endurance of hip replacement. In the present work, Finite Element Analysis was performed on cemented THA with CoCrMo trapezoidal, CoCrMo circular, Ti6Al4V trapezoidal and Ti6Al4V circular stem. It was observed that cross section and material of femoral stem proved to be critical parameters for stress distribution in femoral components, distribution of interfacial stress and micro movements. In the first part of analysis, designs were investigated for micro movements and stress developed, for different stem materials. Later part of the analysis focused on investigations with respect to different stem cross sections. Femoral stem made of Titanium alloy (Ti6Al4V) resulted in larger debonding of stem at cement-stem interface and increased stress within the cement mantle in contrast to chromium alloy (CoCrMo) stem. Thus, CoCrMo proved to be a better choice for cemented THA. Comparison between CoCrMo femoral stem of trapezium and circular cross section showed that trapezoidal stem experiences lesser sliding and debonding at interfaces than circular cross section stem. Also, trapezium cross section generated lower peak stress in femoral stem and cortical femur. In present study, femur head with diameter of 36 mm was considered for the analysis in order to avoid dislocation of the stem. Also, metallic femur head was coupled with cross linked polyethylene liner as it experiences negligible wear compared to conventional polyethylene liner and unlike metallic liner it is non carcinogenic. © 2015, The Institution of Engineers (India).